Crystal structures of zinc(II) coordination complexes with isoquinoline N-oxide - Erin N. Groneck; Nathan Peek; Will E. Lynch; Clifford W. Padgett (Acta Crystallographica Section E: Crystallographic Communications)
The reaction of one equivalent of zinc(II) halide salts with two equivalents of isoquinoline N-oxide (iQNO; C9H7NO) in methanol yields compounds of the general formula [ZnX2(iQNO)2], with X = Cl− (I), Br− (II) and I− (III). However, starting with zinc(II) perchlorate or nitrate leads to the formation of complex ions with the compositions [Zn(iQNO)6](X)2 for X = ClO4− (IV), and [Zn(iQNO)(H2O)5](iQNO)2X2 for X = NO3− (V). Complexes (I), (II) and (III), namely dichloridobis(isoquinoline N-oxide-κO)zinc(II) [ZnCl2(C9H7NO)2], dibromidobis(isoquinoline N-oxide-κO)zinc(II) [ZnBr2(C9H7NO)2], and diiodidobis(isoquinoline N-oxide-κO)zinc(II) [ZnI2(C9H7NO)2], each exhibit a distorted tetrahedral coordination geometry around the zinc(II) ion coordinated by two iQNO ligands bound through the oxygen atom and two halide ions. The zinc ion lies on a crystallographic twofold axis in the bromo complex. The X—Zn—X bond angles are approximately 15–17° larger than the O—Zn—O bond angles resulting in the observed tetrahedral distortion. In complex (IV), hexakis(isoquinoline N-oxide-κO)zinc(II) bis(perchlorate), [Zn(C9H7NO)6](ClO4)2, the zinc(II) ion occupies a special position with 3 site symmetry and is octahedrally coordinated by six iQNO ligands, albeit with slight distortions evidenced by a spread of cis bond angles from 85.82 (4) to 94.18 (4)°. The chlorine atom of the perchlorate anion lies on a crystallographic threefold axis. Finally, complex (V) crystallizes with a pseudo-octahedral geometry; pentaaqua(isoquinoline N-oxide-κO)zinc(II) dinitrate–isoquinoline N-oxide (1/2), [Zn(C9H7NO)(H2O)5](NO3)2·2(C9H7NO). The nitrate ions and non-coordinated iQNO molecules engage in π-stacking and hydrogen-bonding interactions with the coordinated water molecules. The iQNO—Zn—O equatorial bond angles range from 88.98 (9) to 94.90 (9)°, with the largest deviation from a perfect octahedral angle attributed to the influence of a weak C—H...O (from water) interaction (2.287 Å) involving the bound iQNO ligand.